Tourism Potential in the Middle Euphrates Governorates (Karbala, Nabul, and Najaf) and Ways to Develop Them (Zien Journal of Social Sciences and Humanities, 2023)
Many countries and tourist attractions in the world seek to develop tourism products and elements of tourist attractions because of their importance in the economic, social and political aspects, and the study of the tourism potential in the central Euphrates provinces of Iraq, represented by the governorates (Karbala, Babylon and Najaf) is of great importance at the level of the country and the region The study for what it provides in terms of providing job opportunities, reducing unemployment and attracting internal and external investment. It appears from the study that Karbala governorate ranks first in terms of the number of tourist visitors, as it owns (8) religious sites (4 sites) of nature and (5) archaeological sites where tourists come to, while Najaf governorate ranks second in terms of the number of visitors and the number of Tourist hotels and the number of tourist sites (24) a tourist site where the natural sites number (2), archaeological sites (9) and religious sites (13), and Babylon governorate comes third in terms of the number of visitors and the number of tourist hotels despite the large number of many tourist sites, including (20) A tourist site, including the archaeological sites number (4) and the lower sites (16).